Ethical challenges for international collaborative research partnerships in the context of the Zika outbreak in the Dominican Republic: a qualitative case study - Julio Arturo Canario Guzmán; Roberto Espinal; Jeannette Báez; Ricardo Elias Melgen; Patricia Antonia Pérez Rosario; Eddys Rafael Mendoza (BMC, 2017)
Abstract Background The establishment of international collaborative research partnerships in times of infectious disease outbreaks of international importance has been considered an ethical imperative. Frail health research systems in low- and middle-income countries can be an obstacle to achieve the goal of knowledge generation and the search for health equity before, during and after infectious disease outbreaks. Methods A qualitative case study was conducted to identify the challenges and opportunities facing the Dominican Republic with regards to developing international collaborative research partnerships in the context of the Zika outbreak and its ethical implications. Researchers conducted 34 interviews (n = 30 individual; n = 4 group) with 39 participants (n = 23 males; n = 16 females) representing the government, universities, international donor agencies, non-governmental organisations, community-based organisations and medical societies, in two metropolitan cities. Results Five international collaborative research projects related to the Zika virus were identified. Major ethical challenges were linked to the governance of health research, training of human resources, the institutionalisation of scientific activity, access to research funds and cultural aspects. Capacity-building was not necessarily a component of some partnership agreements. With few exceptions, local researchers were merely participating in data collection and less on defining the problem. Opportunities for collaborative work included the possibility of participation in international research consortiums through calls for proposals. Conclusions The Dominican government and research stakeholders can contribute to the international response to the Zika virus through active participation in international collaborative research partnerships; however, public recognition of the need to embrace health research as part of public policy efforts is warranted. A working group led by the government and formed by national and international research stakeholders will be key to identify ways in which the country could respond to the ethical demand of generating new knowledge in times of outbreaks.